2008
DOI: 10.1124/dmd.108.021444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Enzymes Involved in the Metabolism of 17α-Hydroxyprogesterone Caproate: An Effective Agent for Prevention of Preterm Birth

Abstract: ABSTRACT:Preterm delivery, that is delivery before 37 completed weeks of gestation, is the major determinant of neonatal morbidity and mortality. Until recently, no effective therapies for prevention of preterm birth existed. In a recent multicentered trial, 17␣-hydroxyprogesterone caproate (17-OHPC) reduced the rate of preterm birth by 33% in a group of high-risk women. Limited pharmacologic data exist for this drug. The recommended dose is empiric; the metabolic pathways are not well defined especially in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
(9 reference statements)
2
27
0
Order By: Relevance
“…Furthermore, the expression of drug transporters in fetal and adult human hepatocytes was evaluated. Dual-labeled 17-OHPC used in our study was observed to retain both ( 14 C, 3 H) labels after metabolism to mono-, di-, and tri-hydroxy derivatives, the major metabolites generated on incubations with adult and fetal hepatocyte cultures (Caritis et al, 2011 ;Sharma et al, 2008). Thus, the findings in our study refer to the disposition of 17-OHPC and its metabolites; in using the current study design, any difference between the parent compound and its metabolites cannot be differentiated.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, the expression of drug transporters in fetal and adult human hepatocytes was evaluated. Dual-labeled 17-OHPC used in our study was observed to retain both ( 14 C, 3 H) labels after metabolism to mono-, di-, and tri-hydroxy derivatives, the major metabolites generated on incubations with adult and fetal hepatocyte cultures (Caritis et al, 2011 ;Sharma et al, 2008). Thus, the findings in our study refer to the disposition of 17-OHPC and its metabolites; in using the current study design, any difference between the parent compound and its metabolites cannot be differentiated.…”
Section: Discussionmentioning
confidence: 79%
“…Our first aim was to measure the functional activity of hepatic transporters in primary cultures of fetal hepatocytes using sodium taurocholate as a substrate of sodiumdependent uptake transporter, SLC10A1 (NTCP), and the bile salt efflux transporter, ABCB11 (BSEP). Our second aim was to determine whether transport processes were involved in the disposition of 17a-hydroxyprogesterone caproate (17-OHPC), a new progesterone analog administered to pregnant women to prevent preterm delivery (Meis et al, 2003;Sharma et al, 2008). Progesterone metabolites (PMs) have been reported to play a role in the etiology of ICP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in spite of the lower 17-OHPC-metabolizing capability, the results suggest that CYP3A7 may play a major role in the fetal disposition of 17-OHPC. Although CYP3A5 has been observed to metabolize 17-OHPC (Sharma et al, 2008) much more efficiently than CYP3A4, it is less likely to play a significant role in fetal metabolism because the expression level is almost negligible (Hakkola et al, 2001). The relative metabolic capacities of adult and fetal hepatocytes were evaluated by estimating the half-life and intrinsic clearance of 17-OHPC (5 M) based on loss of parent drug experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the full scan and previously published reports (Sharma et al, 2008;Yan et al, 2008) ϩ and its Na ϩ adduct). The results were used in the characterization of the kinetics of 17-OHPC and its metabolites.…”
mentioning
confidence: 99%
“…For these 73 (Table 3). [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] The mean (± S.D.) and median CYP3A5/CYP3A4 ratios of the metabolic activities in these 47 reactions were 0.69 ± 1.23 and 0.28, respectively.…”
Section: Metabolic Activity Of Cyp3a4 and Cyp3a5mentioning
confidence: 99%